Urban Studies and Transformation - Craft, Dominque (New Jersey Clanrye International, 2016)
This book elucidates the concepts and innovative models around prospective developments with respect to urban studies and related transformation. It strives to provide a fair idea about this discipline and to help develop a better understanding of the latest advances within this field. Urban studies is mainly concerned with the sustainable use of land and environment including water, air and infrastructure. This book includes latest studies on urban planning and development. It includes researches and case studies from across the globe to provide the readers with a global outlook on the recent progress of this discipline. Through this book, we attempt to further enlighten the readers about the new concepts in this field. It aims to serve as an essential guide for students and experts alike and contribute to the growth of the discipline.
Keywords: Social Science; Urban Studies